Digital divide decoded: Can e-commerce and remote workforces enhance enterprise resilience in the COVID-19 era? - Long Hai Vo; Thai-Ha Le; Donghyun Park (Asian Development Bank (ADB), 2022)
We examine the adverse impact of coronavirus disease (COVID-19) on the performance of more than 12,000 firms in 32 countries along several dimensions; namely, revenue, production, and labor outcomes. We find that the majority of firms experienced permanent or temporary closures, decreased sales and working hours, reduced production capacity, and worker layoffs. However, the impact was heterogeneous across countries and industries. To explain the diverse firm performance, we identify key factors that significantly contribute to firm resilience during the COVID-19 pandemic, especially access to digital infrastructure. After controlling for firm characteristics, macroeconomic conditions, and pandemic prevalence, we found that firms that have access to digital infrastructure performed better than those that do not. The key channel is an enhanced capacity to adopt electronic commerce business models and employ a larger share of the remote workforce, which boosts resilience during the pandemic when social distancing measures are mandated.
Keywords: M11; L25; H12; 330; organizational reform; digital infrastructure; technology transformation; working from home; labor productivity